A novel tumour suppressor protein encoded by circMAPK14 inhibits progression and metastasis of colorectal cancer by competitively binding to MKK6. Issue 10 (14th October 2021) - Wang, Lu; Zhou, Jiahui; Zhang, Chuan; Chen, Ranran; Sun, Qingyang; Yang, Peng; Peng, Chaofan; Tan, Yuqian; Jin, Chi; Wang, Tuo; Ji, Jiangzhou; Sun, Yueming
Abstract: Background: The mitogen‐activated protein kinase (MAPK) pathway is highly associated with the progression and metastasis of various solid tumours. MAPK14, a core molecule of the MAPK pathway, plays vital roles in the colorectal cancer (CRC). Recent studies have shown that circRNAs can affect tumour progression by encoding peptides. However, little is known regarding the potential protein translated from circMAPK14 and whether it plays a role in the carcinogenesis of colorectal cancer. Methods: The RNA level and translatable potential of circMAPK14 in CRC was verified using qRT‐PCR and public databases. RNase R digestion assay, qRT‐PCR, sanger sequencing and FISH assays were utilised to verify the circular characteristics and subcellular localisation of circMAPK14. The suppressive role of circMAPK14 on the progression and metastasis of CRC was verified in vivo and in vitro. LC/MS analysis combined with western blotting demonstrated the presence and relative expression of circMAPK14‐175aa. The underlying mechanism of circMAPK14‐175aa action to inhibit CRC was identified by co‐IP analysis. The binding of U2AF2 within the flanking introns of circMAPK14 was evaluated by RNA pull‐down assay and RIP assay. Ultimately, luciferase reporter gene assays and ChIP assays confirmed that FOXC1 suppressed transcription of U2AF2 by binding to the U2AF2 promoter in the –400 bp to –100 bp region. Results: We identified that hsa_circ_0131663 (termed circMAPK14) showed significantly decreased expression level in cells and tissue samples of CRC, and was primarily localised in the cytoplasm. A series of function experiments demonstrated that circMAPK14 influenced CRC progression and metastasis by encoding a peptide of 175 amino acids (termed circMAPK14‐175aa). We also found that circMAPK14‐175aa reduced nuclear translocation of MAPK14 by competitively binding to MKK6, thus facilitating ubiquitin‐mediated degradation of FOXC1. Moreover, we described a positive feedback loop in CRC in which elevated FOXC1 expression was caused by reduced circMAPK14‐175aa expression. This, in turn, decreased circMAPK14 biogenesis by suppressing U2AF2 transcription. Conclusion: In summary, we reported for the first time that circMAPK14 functioned as a tumour‐suppressor by encoding circMAPK14‐175aa, which blocked the progression and metastasis of colorectal cancer. Abstract : In summary, we first announced that circMAPK14 functions as a tumour‐suppressor through encoding circMAPK14‐175aa in the progression and metastasis of colorectal cancer.